The effects of idealised images on an individual's aspirations to their ideal self - Nhlapo, Busisiwe (My University, 2017)
The instigation of the dissertation was prompted by the heightened prevalence of idealised images portrayed on social media platforms. It has therefore undertaken a theoretical framework necessary in comprehending the consequential effects idealised images may have on South African millennials. Five research constructs have been developed to form part of the empirical framework, comprising exposure to idealised images, self-esteem, social comparison, self-congruency and aspiration to the ideal self. The use of prior literature relating to the constructs facilitated the formation of a comprehensive review, forming a foundation upon which empirical evidence could be supported. The employment of a quantitative approach necessitated the data be collected through the dissemination of self-administered questionnaires. The sample comprised 500 students from the University of the Witwatersrand, Braamfontein Campus, aged between 18 and 36. Respondents of the study were selected in accordance to a probability sampling technique, upon which the relationship between variables identified in the conceptual model were tested through the adoption of measurement scales. The use of SPSS 24 and AMOS 24 software packages, and structural equation modelling were utilised for the analyses of the data set. The empirical findings derived from the hypothetical tests suggested positive relationships between exposure to idealised images and self-congruency, and self-congruency and aspiration to the ideal self respectively. The relationship between exposure to idealised images and self-congruency was rejected due to the lack of significance and support. Despite the limitations encountered in the study, a blueprint has been provided to future researchers seeking to engage in research bearing similar concepts and segments, leading to the extension of literature and the modification of conceptual constructs. The examination of South African millennials and their constant exposure to idealised images on social media platforms provided an overview of the effects it may have on their behavioural motives. The findings obtained in the study enable brand managers, marketers and academics to comprehend the millennials’ uses and gratifications of social media in a South African context, inclusive of the varying factors that influence the formations of aspiring to their ideal self-concepts.
A Masters dissertation submitted in fulfillment of the requirements for the degree of the Master of Commerce (Marketing) in The School of Economic and Business Sciences, the University of the Witwatersrand. 30 November, 2017
Keywords: Self-esteem; Identity (Psychology)--South Africa; Self-realization